COLLEGE STUDENT MIND-SET AND INTENTIONS TOWARD ENTREPRENEURSHIP IN CHENNAI CITY - Sankar; Sutha, Irin (International Journal of Research -GRANTHAALAYAH, 2016)
The objective of the present paper is to examine the college student Mind-set and intentions toward entrepreneurship, Entrepreneurship is considered as engine of economic growth. That plays a great role in the economic growth and development of the country, more so in a rapidly developing country like India. Entrepreneurship development today has assumed great significance as it is a key to economic development. Entrepreneurs are the seed of industrial development and its fruits are greater employment opportunities, increase in per capita income, higher standard of living and balanced regional development. The present paper attempts to review and analyze the empirical studies undertaken to find out the entrepreneurial intention among college students and find out the factors influencing their decision to venture in entrepreneurship.